The Role of Interactive Methods in Teaching Oratory - Nilufar Babajonova; Muxitdinova Sarvinoz Alisher qizi (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
This article discusses the importance of interactive methods in teaching oratory (speech culture), their effectiveness and role in the educational process. Through interactive methods, students' communication skills, free thinking, and public speaking skills are formed. The article analyzes important interactive methods - role-playing games, debates, discussions, group exercises, and methods for analyzing problem situations. It also substantiates the fact that these methods increase students' activity and expand their ability to express their thoughts fluently and confidently.